Preparation and Quality Evaluation of Soy Corn Yoghurt - Shrestha, Suman Lal; Yadav, Ram Shovit (Himalayan Journal of Science and Technology, 2018)
Soy corn yoghurt is a vegan friendly product prepared by using soymilk as the major ingredient. The aim of this study was to assess the effect of corn milk addition (0, 10, 20, 25 & 30%) on the quality of soy yoghurt. The samples were subjected to sensory evaluation for consumer acceptability and data were subjected to statistical analysis. From sensory evaluation and statistical analysis 10% corn milk inclusion was selected as the best product (p<0.05). The yoghurt thus prepared using 10% corn milk had total solids 22.04%, moisture content 78.62%, protein 4.84%, fat 3.29%, carbohydrate 12.57%, ash 0.81%, acidity 0.68% and pH 4.58. Both control and 10% corn milk incorporated yoghurts were stored under refrigeration 6±1° C and analyzed at 2 days interval till 10 days. Yoghurts with corn milk and control were organoleptically acceptable up to 10 and 6 days respectively. Acidity and syneresis increased but pH decreased with storage time in both samples.